Evaluation of diagnostically difficult impacted maxillary canines in orthodontic patients and its effect on the root of adjacent teeth using cone beam computed tomography - Zahra Dalili Kajan; Ali Khalighi Sigaroudi; Navid Karimi Nasab; Zhaleh Shafiee; Somayeh Nemati (Wolters Kluwer Medknow Publications, 2014)
Purpose: To evaluate the morphology of apical portion of impacted maxillary canines and their effects on root resorption of adjacent teeth as well as their locations and inclinations with cone beam computed tomography (CBCT) in an individual group of orthodontic patients. Materials and Methods: In this descriptive cross-sectional study, 71 diagnostically difficult impacted canines of 55 orthodontic patients were studied with CBCT images. In this group, the orthodontic treatment approaches for eruption of their impacted teeth were not successful. A radiologist opined about the angulation, the position of apical and coronal portion of maxillary canine tooth, resorption of adjacent teeth as well as existence of apical hook and root curvature in reconstructed images. The simultaneous existence of hook and root resorption with other data was subjected to statistical analysis by Chi-square and Fisher's Exact tests. Results: In this cross-sectional study, the position of crown in buccopalatal dimension were respectively 16.9, 73.2 and 9.9% in buccal, palatal and middle portion of the alveolar bone. Apical hook was seen in 28.2% of cases. Root resorption of the adjacent teeth was induced in 32.3% of the cases, 69.6% of which were slight. Overall, there were no significant statistical differences between the presence of hook, and the positions and angulations of impacted teeth. Conclusions: Apical and palatal positions of crowns of the impacted maxillary canines were the most common locations in the selected groups. The possibility of root resorption of adjacent teeth could be related to angulation of impacted tooth.